James VII's Multiconfessional Experiment and the Scottish Revolution of 1688–1690. Issue 341 (July 2015) - Raffe, Alasdair
Abstract Recently, historians have contended that the Scottish revolution of 1688–90 was at least as radical as the simultaneous revolution in England. This article makes a complementary claim: that James VII and II's policy of tolerating almost all Christian worship, which was introduced first in Scotland, had a greater impact in the northern kingdom than has previously been recognized. Using hitherto unexamined local church court papers, the article argues that James's indulgences of 1687 initiated a 'multiconfessional experiment', a period of largely unfettered competition between religious groups that lasted until the overthrow of the king in the revolution. Not only Scotland's small Catholic and Quaker communities, but also a large body of presbyterian dissenters, benefited from this multiconfessionalism. The revival of presbyterianism ultimately allowed for the re‐establishment of presbyterian government in 1690. Though there was peaceful coexistence between rival religious groups in 1687–8, the outbreak of religious violence at the revolution suggests that most Scots remained intolerant of cultural difference. The wider importance of James's experiment was to reveal how difficult it was for an established Church accustomed to uniformity to perform vital social functions – including poor relief and moral discipline – in conditions of religious pluralism.